Percutaneous ventricular assist device TandemHeart™™ in severe refractory cardiogenic shock. (April 2011) - Meyer, Anna L; Williams, Matthew L; Slaughter, Mark S
Evaluation of: Kar B, Gregoric ID, Basra SS, Idelchik GM, Loyalka P: The percutaneous ventricular assist device in severe refractory cardiogenic shock. J. Am. Coll. Cardiol. 57, 688––696 (2011). Mortality in patients suffering from cardiogenic shock remains high. The article by Kar et al. presents the results of the largest number of patients in a single-center experience receiving percutaneous ventricular assist device support in cardiogenic shock, despite intra-aortic balloon pump and/or high-dose vasopressors and inotropic therapy. Hemodynamic improvements with the use of the TandemHeart™™ (Cardiac Assist Technologies, Inc., PA, USA) device were well documented. The salvage rate for this cohort of patients, the majority of whom would have died without rapid implementation of mechanical circulatory support, was remarkable. As would be expected for application in refractory shock, there was also a high rate of mortality and adverse events. Nonetheless, the authors have demonstrated that the rapid deployment of mechanical circulatory assistance can positively influence outcomes in refractory cardiogenic shock.